Numerical investigation of fluid flow and heat characteristics of a roughened solar air heater with novel v-shaped ribs - Allauddin, Usman; Khan, Waqar; Ali, Saim E.; Haider, Syed Muhammad Mehdi; Ahmed, Abdul S.; Rehman, Abdur; Verdin, Patrick G. (Canadian Science Publishing, 2022)
Solar air heaters convert clean solar energy into useful heat and have a wide range of applications. Computational Fluid Dynamics (CFD) can aid in the design and development of solar air heaters with optimized thermal efficiency. A detailed numerical study was conducted to investigate the fluid flow and heat transfer characteristics of a roughened solar air heater with novel V-shaped ribs having staggered elements. Three dimensional steady-state numerical simulations were performed using the k– RNG turbulence model, and results were found in excellent agreement with experimental data. The effect of ribs spacing were studied through varying the rib pitch to rib height ratio P/e= 6 to 14, for Reynolds numbers (Re) in the range of 4000-14,000. A significant enhancement in the ribs-roughened solar air heater’s thermal performance was observed. It was also established that an increment in P/e from 6 to 10 increases the Nusselt number (Nu) for all Re values investigated. About 72.6% Nu enhancement was predicted for P/e=10 at Re = 12,000. It was further observed that an increment in p/e from 10 to 14 decreases Nu for all Re values considered.
Keywords: Solar air heater; heat transfer enhancement; surface enlargement elements; ribs; Nusselt number